Poetics of psychologicalism of male characters (based on the story "Beauty and Power" by Volodymyr Vynnychenko) (Literatures of the World: Poetics, Mentality and Spirituality, 2017)
The article represents artistic devices that reveal inner world of the male characters in the novel «Beauty and strength» by Volodymyr Vynnychenko. Based on the Carl Jung’s theory of archetypes, the author made an attempt to trace the personation of the characters’ selfhood and shadow that appear in conflict situations in the novel.
Keywords: masculinity; psychologism; archetype; affect; selfhood; shadow